재난안전마을 구축을 위한 의식조사 연구 - 구원회; 백민호; Koo, Wonhoi; Baek, Minho (한국재난정보학회 논문집, 14(3), 2018)
Purpose: The purpose of this study is to examine the directions for establishing a disaster safety village in rural areas where damage from a similar type of disaster occurs repeatedly by conducting the consciousness survey targeting at experts and disaster safety officials in a local government. Method: The risks of disaster in rural areas were examined and the concept and characteristics of disaster safety village which is a measure on the basis of Myeon (township) among the measures of village unit were examined in order to carry out this study. In addition, opinion polling targeting at officials-in-charge in the local government and survey targeting at experts in disaster safety and building village were conducted. Based on the findings, the directions for establishing a disaster safety village that fitted the characteristics of rural areas were examined. Result: The officials-in-charge in the local government answered that rural areas have a high risk of storm and flood such as heavy snowing, typhoon, drought, and heavy rain as well as forest fire, and it is difficult to draw voluntary participation of farmers for disaster management activities due to their main duties. They also replied that active support and participation of residents in rural areas are necessary for future improvement measures. The experts mostly replied that the problem of disaster safety village project is a temporary project which has low sustainability, and the lack of connections between the central government, local governments and residents was stressed out as the difficulties. They said that measures to secure the budget and the directions of project promotion system should be promoted by the central government, local governments and residents together. Conclusion: The results of this study are as follows. First, a disaster safety village should be established in consideration of the disaster types and characteristics. Second, measures to secure the budget for utilizing the central government fund as well as local government fund and village development fund should be prepared when establishing and operating a disaster safety village in rural areas. Third, measures to utilize a disaster safety village in rural areas for a long period of time such as the re-authorization system should be prepared in order to continuously operate and manage such villages after its establishment. Fourth, detailed measures that allow residents of rural areas to positively participate in the activities for establishing a disaster safety village in rural areas should be prepared. 연구목적 : 본 연구는 유사 유형의 재난으로 반복적인 피해가 발생하는 농촌지역에 재난안전마을을 구축하기 위해 전문가 및 지방자치단체 재난안전 담당자 의식조사를 통해 구축방향을 검토하고자 함이다. 연구방법 : 본 연구를 수행하기 위해 농촌지역의 재난 위험성을 살펴보고 마을단위의 대책 중 면단위의 대책인 재난안전마을에 대한 개념 및 특성을 검토하였다. 또한 지방자치단체 담당자를 대상으로 의견조사와 재난안전 및 마을만들기 전문가를 대상으로 설문조사를 실시하였다. 이를 바탕으로 농촌지역 특성에 맞는 재난안전마을 구축 방향을 검토하였다. 연구결과 : 본 연구의 결과에서 지방자치단체 담당자 의견을 살펴보면 농촌지역은 폭설, 태풍, 호우 등의 풍수해와 산불에 의한 위험성이 높다고 응답하였고 농민의 주 업무로 인해 재난관리활동의 자발적인 참여가 어렵다고 응답하였다. 향후 개선대책에는 농촌지역 주민의 지원 및 참여가 적극적으로 이루어져야 한다고 응답했다. 전문가의 의견을 살펴보면 재난안전마을 사업의 문제점은 단발성 공모사업 위주로 사업이 지속성이 떨어진다는 의견이 가장 높았으며 애로사항은 중앙, 지자체, 주민의 연계성이 부족하다고 응답하였다. 또한 적절한 예산확보방안은 정부, 지자체, 주민이 함께 추진해야한다고 응답하였으며 사업추진체계 방향은 중앙정부, 지자체, 주민이 함께 추진해야한다고 응답하였다. 결론 : 본 연구에 대한 결과는 다음과 같다. 첫째, 재난유형 및 특성을 고려한 재난안전마을이 구축되어야 한다. 둘째, 농촌지역 재난안전마을 구축 및 운영 시 중앙정부뿐만 아니라 지방정부, 마을 조성 기금까지 활용할 수 있는 예산확보 방안이 마련되어야 한다. 셋째, 농촌지역 재난안전마을 구축 후 지속적으로 운영 및 관리를 위해 재공인제도 등 장기적으로 활용할 수 있는 방안이 마련되어야 한다. 넷째, 농촌지역 주민이 재난안전마을 구축을 위한 활동에 적극적으로 참여할 수 있는 세부적인 대책이 마련되어야 한다.